2014
DOI: 10.4300/jgme-d-13-00329.1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Postinterview Correspondence From Residency Program Applicants and Subsequent Applicant Match Outcomes

Abstract: Background Studies show postinterview communication from applicants may affect their placement on the program's National Resident Matching Program (NRMP) rank order list. Objective To determine whether postinterview correspondence from applicants to a residency program is associated with the applicant's subsequent position on the program's rank list. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…In terms of postinterview communication, previous studies also reveal findings similar to ours, with approximately 60% to 70% of applicants engaging in postinterview communication despite evidence that engaging in this behavior bears no association with Match success. 14,15 This may not be surprising, as prior studies have revealed that at least half of applicants exaggerate their interest in programs in order to improve their chances of matching favorably, with less than 10% of PDs actually believing students' proclaimed interest. 7,16 Our findings suggest that many students continue to express interest or proclaim high rank to programs because of their perception that it may improve their match success; however, the fact that 51% of our survey respondents would prefer programs to prohibit candidates from notifying them of their high rank (in contrast to the 27% who clearly stated they would not prefer this) suggests that this form of postinterview communication may not only be disingenuous at times, but may also be distressing.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of postinterview communication, previous studies also reveal findings similar to ours, with approximately 60% to 70% of applicants engaging in postinterview communication despite evidence that engaging in this behavior bears no association with Match success. 14,15 This may not be surprising, as prior studies have revealed that at least half of applicants exaggerate their interest in programs in order to improve their chances of matching favorably, with less than 10% of PDs actually believing students' proclaimed interest. 7,16 Our findings suggest that many students continue to express interest or proclaim high rank to programs because of their perception that it may improve their match success; however, the fact that 51% of our survey respondents would prefer programs to prohibit candidates from notifying them of their high rank (in contrast to the 27% who clearly stated they would not prefer this) suggests that this form of postinterview communication may not only be disingenuous at times, but may also be distressing.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] For this reason, the frequency and nature of peri-interview communication between applicants and residency programs has been studied across various specialties. [5][6][7][8][9][10][11][12] Otolaryngology is a highly competitive specialty with a limited number of available residency positions compared to the number of applicants. Therefore, an evaluation of peri-interview communication in the otolaryngology Match is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Applicants feel pressure to contact programs because they believe it will improve their ranking, but there is little evidence to support this assumption. [7][8][9] In our survey, only 5.2% (14 of 268) of program directors reported that they always or usually move applicants up their rank order lists after the applicant promises to rank their program No. 1.…”
Section: Communications From Applicants To Residency Programsmentioning
confidence: 99%